Novel Adlay Bran peptides-based Zinc Supplement: optimization of the preparation procedure, structural identification, stability, and Zinc transport ability in vitro - Bin Du; Haijun Chen; Yunan Li; Changqiong Deng; Yeling Li; Dong Lin (International Journal of Food Properties)
In this study, adlay rice bran-zinc chelate (ABP-Zn) was prepared as a novel and effective zinc supplement to mitigate environmental pollution and reduce the wastage of protein resources during adlay rice production. Under optimal conditions, i.e. time = 60 min, peptide-to-zinc mass ratio = 3:1, pH = 6.0, temperature = 60°C, the Zn content of the ABP-Zn chelate reached 53.52 ± 3.32 mg/g. The ABP-Zn chelate was formed as a result of the bonding of the carbonyl, amino, and carboxyl groups with Zn2+. This was demonstrated by fluorescence spectra, X-ray diffraction, ultra-violet spectroscopy, Fourier transform infrared spectroscopy, surface elemental composition, amino acid composition, multiangle analyses, and physical attributes, such as microstructure and particle size. Compared to zinc gluconate and zinc sulfate, the ABP-Zn chelate exhibited increased stability under various temperatures, pH, and simulated digestive digestion conditions. Furthermore, ABP-Zn significantly promoted the transport of zinc in the Caco-2 cell model. These findings suggest that zinc-binding peptide derived from adlay rice protein has great potential to be used as an ingredient in zinc supplements.